Tourism images and tourist response behaviour: A case of Sabah, Malaysia - Muhammad Faizul Hakimi Kamaruzzaman; Noorsyuhadah Shahrel; Nur Aliah Abdul Shukor; Wong Hao Jun (2021)
The country image is one of the components that can influence a tourist to revisit a destination. The tourism image is the first thing a tourist will see before travelling to a country, and it can directly reflect a country's positive and negative attributes. Thus, this study investigates the country, tourism and hotel image component that affects the response behaviour of tourists in Sabah, Malaysia. A Google form survey is distributed to 215 respondents. Later, data is analysed by using SPSS. Data gathered are tested using descriptive, Cronbach alpha, and correlation test. The result revealed that country image, destination image, and hotel image influence tourist response behaviour. This study is believed to provide a great contribution towards tourist destination, particularly tourism Sabah and related parties, in improving the destination image, services, and facilities in the tourism industry in Sabah, Malaysia.